Fluoride Content in Bottled Waters Used in the Nutrition of Infants and Toddlers - E. Oganessian; R. Ivančaková; M. Koštířová; Z. Broukal (Czech Dental Chamber, 2007)
Fluoride content of bottled waters from the customers foodproducts basket in the Czech Republic 2005-2006 was analysed electrochemically. It was found that bottled waters for infants contained no more than 0.1 mg of fluoride per litre as well as the substantial part of bottled spring waters suitable for infants. An exception is the brand GOOD WATER (Dobrá voda) which contained about under 0.7 ppm of fluoride. The recognizable fluoride content was additionally found in croatian product RADENSKA (0.3-0.6 ppm of fluoride). The regular and exclusive utilization of the above waters in the infants'nutrition ought to modify the dosage scheme of fluoride supplementation if indicated.